2012
DOI: 10.1002/srin.201200120
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Sensitivity of Pre‐Strained AISI 301LN2B Metastable Austenitic Stainless Steel

Abstract: The dynamic behavior of AISI 301LN2B (EN 1.4318) metastable austenitic steel grade has been investigated at 296 K by means of servohydraulic tensile and split Hopkinson bar testing in the strain rate range 0.005–1000 s−1. As delivered, as well as 10% uniaxial, biaxial, and plane strain pre‐strained conditions, without subsequent heat treatment have been tested. A negative strain rate sensitivity is observed in the low strain rate range between 10−4 and 1–10 s−1. Pre‐straining reduces the magnitude of the adiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It is observed that high strain rates promote the formation of stacking faults and ϵ ‐martensite, however suppress α ′‐martensite in 1.4301 . Figure reveals a systematic investigation on the mechanical behavior of steel grade 1.4318 at the strain rates between 6.0 × 10 −4 s −1 and 920 s −1 . As shown in Figure a, in the low strain rate region from 1.6 × 10 −4 s −1 to 0.8 s −1 , the negative strain rate sensitivity at high deformation strain is very pronounced.…”
Section: Trip Effect In Meta‐stable Austenitic Stainless Steelsmentioning
confidence: 88%
See 2 more Smart Citations
“…It is observed that high strain rates promote the formation of stacking faults and ϵ ‐martensite, however suppress α ′‐martensite in 1.4301 . Figure reveals a systematic investigation on the mechanical behavior of steel grade 1.4318 at the strain rates between 6.0 × 10 −4 s −1 and 920 s −1 . As shown in Figure a, in the low strain rate region from 1.6 × 10 −4 s −1 to 0.8 s −1 , the negative strain rate sensitivity at high deformation strain is very pronounced.…”
Section: Trip Effect In Meta‐stable Austenitic Stainless Steelsmentioning
confidence: 88%
“…Meta‐stable ASS show a negative strain rate sensitivity, which means the tensile strength declines as the strain rate increases . The main reason is that adiabatic heating at high strain rates reduces the chemical driving force for martensitic transformation .…”
Section: Trip Effect In Meta‐stable Austenitic Stainless Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the quasi-static strain rate of 2.5 × 10 −4 s −1 , the flow stress of the material increases significantly at around 0.1 true strain, and the strain-hardening rate increases until it reaches a maximum at around 0.25 true strain, after which the hardening rate starts decreasing. The increase in the strain-hardening rate can be related to the phase transformation of austenite to martensite, i.e., the transformation of a soft phase into a much stronger phase [22,23]. Increasing the strain rate decreases the phase transformation rate, and consequently decreases the strain-hardening rate of the material [24].…”
Section: Simultaneous Full-field Strain and Temperature Measurementsmentioning
confidence: 99%
“…Type 304 austenitic stainless steels are extensively used in various industries, such as petroleum, chemistry, power generation, and nuclear industries, due to their good combination of mechanical properties, corrosion resistance, and weldability [1][2][3][4]. In addition, many work clearly showed that the austenitic phase (c) in the 304 stainless steels is metastable.…”
Section: Introductionmentioning
confidence: 99%